Diseño Metodológico para la valoración de empresas de construcción - Cueva Cachi, Lilian Ivonne (2017)
ABSTRACT The work carried out constitutes a methodological design for valuation of companies in the field of construction. The main objective is to have a methodology to determine the value of a company in the construction sector, in order to meet the need for information that partners have and thus have a better knowledge of the situation and perspective of the company. The methodological design chosen to value companies in the construction sector is the Discounted Cash Flow method, which is the accepted method for financial experts, since it allows determining the approximate value of the company, according to its future flows and Either by project or for a company as a whole, discounting it through a certain rate. To validate the methodological design, financial information was used by CG Constructores y Asociados SAC from the years 2013 to 2016. A detailed analysis of each of these reports was made, taking as reference the macroeconomic projections such as: Inflation, Interest and Gross Domestic Product. The results correspond to the value of the Company projected for the years 2017, 2018, 2019 and 2021.